Towards the adoption of drones in foodservice industry: A generic model development - Jasim N.I.; Kasim H.; Mahmoud M.A. (Little Lion Scientific, 2023)
Drone technologies have recently received a great deal of attention due to their high mobility, low cost, and flexible deployment. It is anticipated that drones will be part of our daily life, just like smartphones. The wide deployment of drones in different domains such as healthcare, agriculture, traffic monitoring, firefighting, national defense, rescue activity, and delivery services such as food and retail. Drones are expected to have a significant contribution to food delivery services by saving time, cost, environment, and people's life by reducing traffic congestion, wages, carbon emission, and accidents, respectively. Recently, big corporations, such as Amazon and DHL, have deployed drones as an alternative to traditional delivery methods. However, service providers of drone food delivery (DFD) services need to identify significant factors that influence potential consumers' to use drone delivery. Existing models lack a comprehensive basic theory that addresses factors that influence consumers' intention and behavior. To overcome this limitation and propose a more comprehensive model, relevant research studies from the domain of drone delivery services and other emerging technology such as IoT, Autonomous Vehicles, and Mobile Banking are identified, reviewed, analyzed, and ten potential factors are subsequently extracted. The model is expected to inspire food-service sub-sectors in planning for the adoption of drone technology adoption in evaluating an existing DFD or developing a new one. 2021 Little Lion Scientific